2020
DOI: 10.7554/elife.51217
|View full text |Cite
|
Sign up to set email alerts
|

Eya2 promotes cell cycle progression by regulating DNA damage response during vertebrate limb regeneration

Abstract: How salamanders accomplish progenitor cell proliferation while faithfully maintaining genomic integrity and regenerative potential remains elusive. Here we found an innate DNA damage response mechanism that is evident during blastema proliferation (early- to late-bud) and studied its role during tissue regeneration by ablating the function of one of its components, Eyes absent 2. In eya2 mutant axolotls, we found that DNA damage signaling through the H2AX histone variant was deregulated, especially within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 76 publications
4
31
0
Order By: Relevance
“…In the axolotls regeneration context, cell proliferation is increased in amount and speed which supposes the replication of an immense genome with more than 60% of repetitive sequences in a shorter time, therefore, the DNA repair mechanisms must be efficient enough to counteract all of the DNA insults that could compromise cell viability, induce senescence, and even affect complete and functional regeneration, this is supported by recent findings in limb regeneration where a variety of genes involved in DDR have been identified up-regulated, including the histone H2AX and its phosphorylation. 35 These results correlate with the observation of senescent cells in proliferative blastema cells of axolotls and newts. 59 Although these observations strongly suggest an important participation of DNA damage response pathways during tissue regeneration, the contribution of the diverse DNA repair mechanisms to achieve successful regeneration has not been elucidated yet.…”
Section: Conclusive Remarkssupporting
confidence: 80%
See 2 more Smart Citations
“…In the axolotls regeneration context, cell proliferation is increased in amount and speed which supposes the replication of an immense genome with more than 60% of repetitive sequences in a shorter time, therefore, the DNA repair mechanisms must be efficient enough to counteract all of the DNA insults that could compromise cell viability, induce senescence, and even affect complete and functional regeneration, this is supported by recent findings in limb regeneration where a variety of genes involved in DDR have been identified up-regulated, including the histone H2AX and its phosphorylation. 35 These results correlate with the observation of senescent cells in proliferative blastema cells of axolotls and newts. 59 Although these observations strongly suggest an important participation of DNA damage response pathways during tissue regeneration, the contribution of the diverse DNA repair mechanisms to achieve successful regeneration has not been elucidated yet.…”
Section: Conclusive Remarkssupporting
confidence: 80%
“…Remarkably, the level of γ-H 2 AX does not correlate with those of comet assay, a test used to determine DNA strand breaks, at 14 dpa. 35 However it has to be considered that critics are emerging on using only the comet assay as the technique to evaluate DNA damage, due to its lack of reproducibility, as evidenced in several publications. [36][37][38][39][40][41] Therefore the opposite observations in Sousounis et al, 35 study suggest that further research, using diverse techniques besides comet to asses DNA damage, are needed to fully evidence which DNA insults are occurring in blastema cells and if they are being efficiently repaired in some cells, while in other they accumulate perhaps leading to cell senescence.…”
Section: Maintenance Of Genomic Stability In Blastema Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of EYA-promoted DNA damage repair in normal physiology has been investigated in a limited number of contexts. Local hypoxia during organ development is known to induce replication stress and DNA damage and EYA-promoted damage repair is seen during kidney development (Cook et al 2009) and in limb regeneration (Sousounis et al 2020). Angiogenesis is another developmental process in which an association between hypoxia, DNA damage and repair has been observed (Economopoulou et al 2009).…”
Section: H2axmentioning
confidence: 99%
“…How regenerating tissues are resistant to tumor formation in organisms with a high level of regeneration is not well understood. A recent elegant study showed that salamanders possess an innate DNA damage response mechanism active in the blastema to facilitate proper cell cycle progression upon injury (Sousounis et al, 2020). Tumor suppressors may also play an important role by contributing to the elimination of abnormal cells during regeneration and regulation of senescence (Hesse et al, 2015;Sarig et al, 2019;Shoffner et al, 2020;Yun et al, 2015;Yun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%